Junction temperature control of UV-C LEDs based on a thermoelectric cooler device. (July 2019) - Fredes, P.; Raff, U.; Gramsch, E.; Pascal, J.; Cuenca, J.
Abstract: Junction temperature ( T J ) control is mandatory to improve the optical efficiency, lifetime and the wavelength accuracy of the UV-C LED light sources. Thermoelectric cooler devices allow a critical control of the junction temperature, based on direct measurement of the solder point temperature. A PID control technique was implemented to control the voltage in the TEC devices and therefore the desired range of junction temperatures. The PID parameters are obtained with computational simulations based on physical models and experimental recordings of the solder temperature dynamics. Optical performance improves is demonstrated and the better lifetime could be achieved.